PENYULUHAN TIPS DAN TRIK PENGGUNAAN E-COMMERCE UNTUK PENGEMBANGAN UMKM MASYARAKAT DESA SIDOMULYO KECAMATAN SEMBORO KABUPATEN JEMBER DI ERA PANDEMI COVID-19 - Ahmad Sauqi (STIE Mandala Jember, 2021)
This service seeks to solve the problems of MSMEs in Sidomulyo village by providing counseling on the theme of tips and tricks for using e-commerce for community development in Sidomulyo Village, Semboro District, Jember Regency in the era of the Covid-19 pandemic. The results of this trial included the MSME community in the village of Sidomulyo Semboro Jember stated that their products were selling well compared to before the existence of E-Commerce counseling, MSME players in Sidomulyo Village stated that they had started a lot of these things they felt by ordering them. more and more every week. MSME players in Sidomulyo Village stated that marketing products through E-Commerce is easy if you learn to just post in the Facebook buying and selling group, put it on the Facebook market place or sell it through shopee or tokopedia. Keywoard: Tips; Tricks; E-Commerce; UMKM; Sidomulyo